Childhood attachment and behavioral inhibition: Predicting intolerance of uncertainty in adulthood. (21st November 2017) - Zdebik, Magdalena A.; Moss, Ellen; Bureau, Jean-François
Abstract: Intolerance of uncertainty (IU), the tendency to react negatively to uncertain situations, has been identified as an important cognitive component of anxiety disorders, yet little is known about its etiology. Links to temperament, particularly behavioral inhibition (BI), and insecure attachment have been proposed in the development of IU, but no prospective empirical investigation has been performed thus far. In the current study, attachment to caregiver and BI of 60 children were assessed at age 6, using observational measures. Mother's anxiety symptoms were assessed when participants were 14 years old. IU was reported by participants when they were 21 years old, as was neuroticism. Two types of insecure attachment (ambivalent and disorganized–controlling) and BI were positively related to IU over a 15-year span, even after controlling for participants' neuroticism and maternal anxiety. Attachment and BI had no significant interacting effect on the development of IU. Maternal anxiety was positively related to child BI and insecure attachment, but not IU. This study is the first to provide empirical support for a link between ambivalent and disorganized–controlling attachment and BI in preschool children to the development of IU in adulthood. Results have etiological and preventative implications not only for anxiety disorders but also for all disorders related to IU.